Discovering Sustainable Beyond the Food Festivals: A Case Study on the Keuken Food Festival in Bandung - Elena Kartika Sari; Gery Dewanto; Fitra Ananta Sujawoto (Politeknik Pariwisata Makassar, 2024)
Food festival waste has been a big challenge nowadays. Food festivals that support the culinary tourism industry should give special attention to sustainability and also the awareness of environmental impacts such as the number of foods consumed at the event. Ideally, effective food festival waste management should significantly prevent and reduce that and ensure as much as possible is prevented, reduced, and reused based on Sustainable Development Goals (SDGs). Keuken is one of the most popular food festivals in Bandung, West Java, Indonesia annually held the culinary festival 13 times from the year of 2011 until the 13th event in 2024. The novelty of this study is to discover the contribution and implementation of sustainability beyond the festivals. This study used a descriptive analysis method with a qualitative approach. The findings indicate and also provide valuable best practices and methods to implement Sustainable Development Goals (SDGs) on the food festivals, especially on the 12th goal “Ensure sustainable consumption and production patterns”.